1991
DOI: 10.1159/000153994
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Heredity in Myopia

Abstract: A series of 109 like-sexed twin pairs in the age group 30–31 years (54 monozygotic and 55 dizygotic) with one or both members of the twins with myopia was found in the Finnish Twin Cohort. The series was based on a random sample of 1,200 twins in one age stratum of the cohort. The twins received a questionnaire on their health status with special reference to eye diseases and symptoms. The refractive status of the twin pairs was ascertained by asking the twins to send their latest prescription for glasses to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 5 publications
1
57
0
Order By: Relevance
“…The influence of genetic factors on the development of myopia has been supported by twin studies. 4,15,16 The only other study on myopia carried out in Greece also supported the association of parental family history with myopia. 10 However, Saw et al 17 showed that, although parental myopia was significantly related to offspring myopia, the relationship became nonsignificant when adjusted for educational level and other environmental factors.…”
Section: Eyementioning
confidence: 85%
“…The influence of genetic factors on the development of myopia has been supported by twin studies. 4,15,16 The only other study on myopia carried out in Greece also supported the association of parental family history with myopia. 10 However, Saw et al 17 showed that, although parental myopia was significantly related to offspring myopia, the relationship became nonsignificant when adjusted for educational level and other environmental factors.…”
Section: Eyementioning
confidence: 85%
“…Proof for heritability of myopia is a study of monozygotic and dizygotic twin pairs in Finland (Teikari et al 1991). A greater percentage of concordant pairs (both twins myopes or both emmetropes) among monozygotic twin pairs was found compared to dizygotic twin pairs.…”
Section: Discussionmentioning
confidence: 99%
“…A total number of 1852 questionnaires were distributed to students in order to collect data on their refractive condition. We consider the questionnaire method to be of sufficient validity, taking into account that certain other studies were based on this method (Teikari et al 1991;Zadnik et al 1994).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations